Exploring liminality in the co-design of rehabilitation environments: The case of one acute stroke unit. (November 2021) - Donetto, Sara; Jones, Fiona; Clarke, David J.; Cloud, Geoffrey C.; Gombert-Waldron, Karolina; Harris, Ruth; Macdonald, Alastair; McKevitt, Christopher; Robert, Glenn
Abstract: This paper describes an Experience-based Co-design (EBCD) project that aimed to increase patient activity within an acute stroke unit. We apply the concept of liminality to explore ways in which the EBCD process, a form of Participatory Action Research, may dilute or even dissolve social hierarchies and challenge assumptions about practices and constraints in this care setting, thereby opening up possibilities for transformation that enhances the therapeutic value of the space for patients and care providers alike. By occasioning a liminal phase of possibility for change, the work of one co-design group explored in detail here suggests that, in this process, the sociomaterial interactions involving patients, family members, staff, and the physical space are refashioned and re-inscribed in transformed 'emplaced' relationships of care. Highlights: EBCD improved an acute stroke unit environment to provide greater opportunity for social and therapeutic activity. The structured EBCD approach provided a 'liminal' space within which collaborative change could be enabled. Liminality facilitated trust and built a sense of community between participating patients, families and staff. The different roles adopted by participants during the process challenged norms and effected change.